2020
DOI: 10.14336/ad.2020.0317
|View full text |Cite
|
Sign up to set email alerts
|

Immune Characteristics of Patients with Coronavirus Disease 2019 (COVID-19)

Abstract: Up to now, little is known about the detailed immune profiles of COVID-19 patients from admission to discharge. In this study we retrospectively reviewed the clinical and laboratory characteristics of 18 COVID-19 patients from January 30, 2020 to February 21, 2020. These patients were divided into two groups; group 1 had a severe acute respiratory syndrome coronavirus 2 nucleic acid-positive duration for more than 15 days (n = 6) and group 2 had a nucleic acid-positive duration for less than 15 days (n = 12). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 19 publications
1
8
0
Order By: Relevance
“…An increase of CD4 + :CD8 + ( Fig. 2 ) as well as IL-6:IL-10 (data not shown) ratios in intubated patients was observed in line with all up to date reports ( Wang et al, 2020a ), ( Liu et al, 2020 ), ( Dong et al, 2020 ), ( Odak et al, 2020 ), ( Song et al, 2020 ), ( Wang et al, 2020b ). Both intubated and non-intubated patients showed a marked reduction of all lymphocyte subsets apart from NK cells the majority of which remained within the normal range for both groups of patients.…”
Section: Discussionsupporting
confidence: 87%
“…An increase of CD4 + :CD8 + ( Fig. 2 ) as well as IL-6:IL-10 (data not shown) ratios in intubated patients was observed in line with all up to date reports ( Wang et al, 2020a ), ( Liu et al, 2020 ), ( Dong et al, 2020 ), ( Odak et al, 2020 ), ( Song et al, 2020 ), ( Wang et al, 2020b ). Both intubated and non-intubated patients showed a marked reduction of all lymphocyte subsets apart from NK cells the majority of which remained within the normal range for both groups of patients.…”
Section: Discussionsupporting
confidence: 87%
“…Of the included reports, 34 (56%) were peer-reviewed journal papers [ 3 , 8 40 ]. Two animal-based, basic science studies were included [ 30 , 41 ] but the overwhelming majority of reports were in humans, for which the most common designs were case-control (n = 26, 43%) [ 10 12 , 14 , 17 , 21 , 23 , 25 29 , 31 , 32 , 37 , 38 , 40 , 42 50 ] and cohort (n = 22, 36%) [ 8 , 13 , 15 , 16 , 20 , 22 , 34 , 36 , 39 , 51 62 ]. 50 studies (82%) considered participants sampled from hospital settings [ 8 , 9 , 11 29 , 31 40 , 42 , 43 , 45 , 46 , 48 50 , 53 , 54 , 56 65 ].…”
Section: Resultsmentioning
confidence: 99%
“…Our previous study revealed that immunological disorders play an important role in the progression of COVID-19 ( 12 , 13 ). The specific pathogenesis of cytokine storm is still unclear.…”
Section: Introductionmentioning
confidence: 99%